2008
DOI: 10.1164/rccm.200707-1069oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Soluble Receptor for Advanced Glycation End Products on Endotoxin-induced Lung Injury

Abstract: RAGE plays an important role in the pathogenesis of LPS-induced lung injury in mice. It was suggested that sRAGE should be tested as a treatment modality in other models of acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
100
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 41 publications
(46 reference statements)
6
100
1
1
Order By: Relevance
“…Similar findings of the effect of RAGE blockade have been observed in hepatic ischemia reperfusion models (33,34). Furthermore, administration of sRAGE attenuated lung injury in a murine model of LPS-induced lung injury suggesting a role for RAGE ligands in the augmentation of lung injury that is blocked by sRAGE (35). These data suggest a role for RAGE ligands in the augmentation of lung injury and should provide an impetus for further research into the relationship between RAGE, RAGE ligands, and the initiation and perpetuation of transplant-associated lung injury.…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings of the effect of RAGE blockade have been observed in hepatic ischemia reperfusion models (33,34). Furthermore, administration of sRAGE attenuated lung injury in a murine model of LPS-induced lung injury suggesting a role for RAGE ligands in the augmentation of lung injury that is blocked by sRAGE (35). These data suggest a role for RAGE ligands in the augmentation of lung injury and should provide an impetus for further research into the relationship between RAGE, RAGE ligands, and the initiation and perpetuation of transplant-associated lung injury.…”
Section: Discussionsupporting
confidence: 78%
“…This study has also shown that sRAGE, a truncated soluble form carrying extracellular ligand-binding domain of RAGE, has protective effects against LPS-induced septic shock in mice. Previous studies using sRAGE demonstrated its beneficial effects on RAGEassociated diseases such as atherosclerosis and inflammation (20,40,41). The treatment with sRAGE reduced the LPS induction of TNF-a and IL-6 and of liver and lung damages and significantly improved survival rate (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…RAGE expressed on bone marrow-derived cells (e.g., monocyte/macrophages) specifically contributes to atherosclerosis, as transplantation of Ager null/Apoe null bone marrow into Apoe null mice results in markedly reduced atherosclerosis compared with those receiving bone marrow from Ager-positive Apoe null mice (47). Administration of sRAGE markedly decreases atherosclerosis and oxidative injury in animal models (11,41,68,71,72). Thus, activation of RAGE by IsoLG-PE could plausibly contribute to the development of atherosclerosis and liver disease associated with hypercholesterolemia or obesity.…”
Section: Discussionmentioning
confidence: 99%